Proteomes of pathogenic Escherichia coli/Shigella group surveyed in their host environments. (October 2014) - Suh, Moo-Jin; Kuntumalla, Srilatha; Yu, Yanbao; Pieper, Rembert
<x xml:space="preserve">Abstract</x> Proteomic studies on Shigella dysenteriae, Shigella flexneri, enterohemorrhagic Escherichia coli and uropathogenic E. coli (UPEC) are reviewed. UPEC causes infections in the urogenital tract, whereas the other species colonize and, to varying degrees, invade the intestinal tract. Type III secretion systems used to breach the mucosal barrier by the intestinal pathogens revealed distinct expression patterns in different host environments. Dynamic adaptations to changes in nutrient availability and oxygen were observed, including increased reliance on anaerobic respiration and mixed acid fermentation in vivo. Utilization of carbon and nitrogen resources by the bacteria varied considerably depending on the host model investigated. Shigellae and UPEC adapted to metal ion sequestration in the mammalian host by enhancing expression of various receptors and transporters for iron and zinc. This appears to reflect the preferred intracellular life stage of Shigella spp. and responses of UPEC to high levels of lipocalin and lactotransferrin in the urinary tract.